ALCOOLISATION CHEZ LES JEUNES ÉLÈVES EN COTE D’IVOIRE : PRÉFÉRENCE ET CONSOMMATION EFFECTIVE - Emmanuel, Diboh; Mathias, Yao Koffi; Antoine, Tako Némé; François, Bakou Niangoran; Berthe, Assi (European Scientific Journal, ESJ, 2013)
To assess the evolution of alcohol consumption among students in Côte d’ Ivoire, an investigation paralleling the preference of subjects and their actual consumption for alcoholic beverages was conducted. A closed questionnaire was administered to 3428 subjects (1458 boys and 1396 girls) divided into three groups according to age: 10 to 14 years old (n = 598), 15 to 20 years old (n = 1769), and 21 to 24 years old (n = 487). Regular alcohol consumption is higher, on the one hand, males (26,13 %) than females (9,60 %) and, on the other hand, in 21 to 24 years (24,44 %) than in the 15 to 20 years (19,84 %) and 10-14 years (7,53 %). Overall, koutoukou is so consumed (9,39 %) as preferred (9,93 %). However dolo (home-made beer) is consumed (8,19 %) and liked it (6,58 %). Conversely, the bangjy is more appreciated (44,22 %) than consumed (19,41 %). As for industrial alcohol, they are more preferred than consumed: 47,48 % vs 33,78 % for beer, 46,6 % vs 27,07 % for wine, 27,72 % vs 17,58 % for the liquor. This behavior is linked to the selling price of different alcohols and their availability on the market.